Would people with Parkinson's disease benefit from palliative care? - Hudson, P.; Toye, Christine; Kristjanson, Linda (Sage Science Press (UK), 2006)
Parkinson’s disease (PD) is a chronic, progressive, degenerative disorder of the nervous system, causing substantial morbidity and has the capacity to shorten life. People with PD and their families can find the disease devastating. Nevertheless, this population of patients is not usually considered a group to be supported by palliative care specialists. But the nature of the illness and the challenges of managing its many physical and psychological effects raises questions about the potential benefits of a palliative care approach. The purpose of this project was to describe the experience of PD and consider the relevance of palliative care for this population. Semi-structured interviews were conducted with eight people with PD, 21 family caregivers and six health professionals. Five themes were developed from the data analysis: (1) emotional impact of diagnosis; (2) staying connected; (3) enduring financial hardship; (4) managing physical challenges; and (5) finding help for advanced stages. These data revealed that people with PD and family caregivers are confronted with similar issues to people with typical palliative care diagnoses, such as advanced cancer, and that a palliative approach may be helpful in the care of people with PD and their families.